Pedagogical implications of students’ misconceptions about deductive geometric proof - Mdutshekelwa Ndlovu; Andile Mji (Acta Academica, 2012)
The role of proof in school geometry has been a subject of intense debate throughout the twentieth century and that debate persists even today. This study aims to identify and analyse deductive geometric proof difficulties encountered by Bachelor of Education (BEd) in-service student teachers and to propose possible ways of remediating them. The authors conducted a content analysis of responses to a circle geometry item in an achievement test taken by 170 students. Although 78% of the students performed well in the deductive proof item, 22% evidenced misunderstandings or misconceptions which varied in complexity. The misconceptions were analysed into four categories and implications for pedagogy proffered to turn the misconceptions into critical teaching and learning opportunities.